Other ergogenic agents - Stricker, P. R. (Clinics in Sports Medicine, 1998)
Amid the surrounding chaos of the supplement blitz, athlete, coach, and physician alike must step back and place the issue of supplements into perspective. There is no legal supplement that can substantially alter performance to date in the same way as illegal drugs. Effectiveness, safety, legality, and purity of compounds are all issues that should be addressed when approaching the use of any supplement. Education about the validity of the claims of supplements is important. Research is lending useful and helpful information despite the many new products continually appearing on the market. Because there is no mechanism for investigations to adequately research every supplement, many of the supplements should be approached with caution and skepticism. In addition, supplements in and of themselves should not be viewed as the sole answer to performance improvement. There is some promise to an extremely small number of supplements that appear to enhance performance, yet they do so in the realm of complete athletic training, including hard work, sports-specific training and strength training, psychological preparedness, and good nutritional intake.